(3CYeGd GdeDJeQ GdYdej GdSfhj dcdjI GdMbhb HLGeYI HjQhJ GdYQHjIs - (3gGfj eMeO(B, (3OhjOGQs ((3HjQhJ(B:s (3efThQGJ GdMdHj GdMbhbjI(B,s, 2002)
(3GdHYO GdOhdj dLQjeI JHjV GdCehGd(B- (3LQjeI JHjV GdCehGd aj GdbGfhf GdLRGFj GddHfGfj(B- (3GdLQGFe GdeJYdbI HGSJNOGe HWGbGJ GdCFJeGf(B.s
Keywords: (3GdHfhc(B- (3GdeDJeQGJ(B- (3dHfGfs; (3GdHfhc(B- (3bhGfjf hJTQjYGJ(B- (3dHfGfs